On the virtual waiting time for an M/G/1 retrial queue with two types of calls. (1993) - Choi Choi, Bong Dae Bong Dae; Han Han, Dong Hwan Dong Hwan; Falin Falin, Guennadi Guennadi
Abstract : We consider an M / G / 1 retrial queueing system with two types of calls which models a telephone switching system. In the case that arriving calls are blocked due to the channel being busy, the outgoing calls are queued in priority group whereas the incoming calls enter the retrial group in order to try service again after a random amount of time. In this paper we find the Laplace-Stieltjes transform of the distribution of the virtual waiting time for an incoming call. When the arrival rate of outgoing calls is zero, it is shown that our result is consistent with the known result for a retrial queueing system with one type of call.